Adaptive Feedback Linearization Controller for Stabilization of Quadrotor UAV - Rahmat, Mohd Fuaad; Eltayeb, Ahmed; Mohd Basri, Mohd Ariffanan (International Journal of Integrated Engineering, 2020)
Due to the various applications of the quadrotor UAV systems increase in a daily basis, the researchers recently granted it a great attention. In this paper, the mathematical model of the quadrotor UAV has been presented. Then, the feedback linearization technique is used to linearize the attitude/altitude dynamic equations of the quadrotor. The PID controller is applied to the linearized model (attitude/altitude subsystems). However, for a robust performance against the wind disturbance and the model parameter uncertainty, the adaptive feedback linearization is proposed and implemented to the attitude/altitude subsystems, and the stability approach of the proposed controller was derived based on a candidate Lyapunov function. Finally, the proposed controller has been tested and verified by simulation Matlab/Simulink and shows a good performance against both uncertainties and disturbances.